2010
DOI: 10.1248/bpb.33.444
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Protection by Basic Fibroblast Growth Factor from Ischemia/Reperfusion-Induced Injury in Diabetic Rats

Abstract: Diabetes impairs the expression and function of endogenous growth factors, leading to increased cardiovascular events in diabetic patients. Supplementation of fibroblast growth factors (FGFs) protected the heart from ischemia/reperfusion (I/R)-induced injury in animal models. However, it has not yet been tested in diabetic heart. The present study was thus to clarify whether basic fibroblast growth factor (bFGF) could protect the heart from I/R-induced damage under diabetic conditions using a rat model. Male S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 45 publications
(73 reference statements)
2
28
0
Order By: Relevance
“…conditions. 30 In a previous study, we have shown that cultured iPSCs can secrete bFGF in vitro. 31 In this study, we demonstrated that the levels of bFGF did not significantly increase at day 3 but did reach significance later, at days 7, 14, and 21, while SDF-1a was upregulated early, at day 3 after iPSC transplantation.…”
Section: Figmentioning
confidence: 96%
“…conditions. 30 In a previous study, we have shown that cultured iPSCs can secrete bFGF in vitro. 31 In this study, we demonstrated that the levels of bFGF did not significantly increase at day 3 but did reach significance later, at days 7, 14, and 21, while SDF-1a was upregulated early, at day 3 after iPSC transplantation.…”
Section: Figmentioning
confidence: 96%
“…3 Acidic fibroblast growth factor (aFGF) is an important member of the FGF family, with a wide range of biological functions, including mitogenic and non-mitogenic activities, and it is expressed at high levels in the heart. 4,5 However, aFGF has powerful mitogenic and proliferative influences and produces negative effects, such as tumor genesis and metastasis. 6,7 Previous studies have shown that aFGF protects the cardiac function in myocardial diseases, such as diabetic cardiomyopathy and post-ischemic reperfusion, with its nonmitogenic activities.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic nephropathy (DN) is associated with hemodynamic and metabolic perturbations caused by hyperglycemia, leading to the development of functional and morphological abnormalities [1][2][3][4] . Oxidative stress (OS) and subsequent cellular damage are postulated to play crucial roles, leading to the development of glomerular and renal injury [5,6] .…”
Section: Introductionmentioning
confidence: 99%